Peran Brand Likeability dalam Memoderasi Hubungan antara Ekuitas Merek dan Kinerja Merek pada Bank Syariah - Alisa, Ziyan Sakinah; Firmansyah, Egi Arvian (Universitas Islam Negeri Sunan Kudus, 2020)
This research aims to find the effect of brand equity towards brand performance moderated by brand likeability, where brand equity is explained by it’s four dimensions, which are brand awareness, brand association, perceived quality and brand loyalty. Using quantitative approach, this research uses questionnaire method with Likert scale and specifically targets customers of Bank Syariah Mandiri. The amount of sample being used in this research is 166 respondents. Before the questionnaire was opened to the public, it was tested by the first 30 respondents, consisting lecturer and students of Islamic Economics major in Padjadjaran University. The obtained data then processed using Structural Equation Modelling (SEM) on AMOS software. The results found that brand equity moderated by brand likeability has a significant effect on brand performance. In addition, among the four dimensions of brand equity, only brand awareness has a significant relationship with brand performance.